Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus 2 IgG in Juba, South Sudan, 2020 - Wiens, Kirsten E.; Mawien, Pinyi Nyimol; Rumunu, John; Slater, Damien; Jones, Forrest K.; Moheed, Serina; isch, Andrea Cafl; Bior, Bior K.; Jacob, Iboyi Amanya; Lako, Richard Lino; Guyo, Argata Guracha; Olu, Olushayo Oluseun; et al. (Emerging infectious diseases, 2021)
Relatively few coronavirus disease cases and deaths have been reported from sub-Saharan Africa, although the extent of its spread remains unclear. During August 10–September 11, 2020, we recruited 2,214 participants for a representative household-based cross-sectional serosurvey in Juba, South Sudan. We found 22.3% of participants had severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) receptor binding domain IgG titers above prepandemic levels. After accounting for waning antibody levels, age, and sex, we estimated that 38.3% (95% credible interval 31.8%–46.5%) of the population had been infected with SARS-CoV-2. At this rate, for each PCR–confirmed SARS-CoV-2 infection reported by the Ministry of Health, 103 (95% credible interval 86–126) infections would have been unreported, meaning SARS-CoV-2 has likely spread extensively within Juba. We also found differences in background reactivity in Juba compared with Boston, Massachusetts, USA, where the immunoassay was validated. Our findings underscore the need to validate serologic tests in sub-Saharan Africa populations.
Keywords: antibodies, coronavirus disease, COVID-19, influenza, Juba, respiratory infections, SARS-CoV-2, seroprevalence, serosurvey, South Sudan, sub-Saharan Africa, severe acute respiratory syndrome coronavirus 2, viruses